The Star Guide: Learn How To Read the Night Sky Star by Star - Kerrod Robin (Wiley, 2005)
A bit oversize for field use, this introduction to stargazing nonetheless offers an informative beginning for learning navigation of the night sky before heading outside. (It comes with a removable hand-size sky map called a planisphere.) Kerrod's presentation is structured around monthly star maps (for midlatitude observers) in two-page spreads, with a follow-up feature on that month's outstanding constellation. So that rather than emphasizing rote memorization of all 88 recognized constellations, the book enables identification of just the most striking constellations, such as Orion or the Northern Cross, making the task of celestial familiarization much easier. The text then instructs viewers in using a constellation's brightest individual stars to orient themselves to neighboring asterisms, progressively cultivating a mental image of the entire celestial vault and its changing appearance over the course of a year. Photos featuring Hubble Space Telescope spectaculars, supplemented by tips for viewing the sun, moon, and planets, round out this attractive book on basic astronomy. Gilbert Taylor